2014
DOI: 10.3109/08916934.2014.883503
|View full text |Cite
|
Sign up to set email alerts
|

Has-mir-146a rs2910164 polymorphism and risk of immune thrombocytopenia

Abstract: The purpose of this study was to determine the association of single nucleotide polymorphisms (SNP) of the has-mir-146a (miR-146a) genes with the risk for immune thrombocytopenia (ITP). The genotyping of miR-146a rs2910164 polymorphism was detected by polymerase chain reaction-restriction fragment length polymorphism. In the patients with ITP, the frequencies of GG, GC and CC genotypes and G and C alleles were 12.5%, 47.9%, 39.6%, 36.4% and 63.6%, respectively. There was no significant difference in genotype a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…SNPs in the miR gene region may directly affect the expression of the mature miRNA, resulting in diverse functional consequences. To date, various epidemiological studies have indicated associations between SNPs in miRNAs and cancer susceptibility [ 3 ], autoimmune diseases [ 8 , 14 ], schizophrenia [ 22 ] and cardiovascular disease [ 19 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…SNPs in the miR gene region may directly affect the expression of the mature miRNA, resulting in diverse functional consequences. To date, various epidemiological studies have indicated associations between SNPs in miRNAs and cancer susceptibility [ 3 ], autoimmune diseases [ 8 , 14 ], schizophrenia [ 22 ] and cardiovascular disease [ 19 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Over the past several years, it has become increasingly clear that miRNAs are not only important for normal organismal development and physiology but also in the pathologies of autoimmune diseases, cancer, heart disease, and inflammation [ 5 7 ]. Regarding autoimmune diseases, it has been reported that many have similar underlying etiology and have shared susceptible genes [ 8 ]. Among all the miRNAs discovered, miR-146a and miR-499 have been received much attention in this field.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation